PENGETAHUAN TENTANG FLUORALBUS DAN PERILAKU PERSONAL HYGIENE REMAJA SANTRI PUTRI PONDOK PESANTREN â€œXâ€ DUKUHWALUH, PURWOKERTO - Nurul Chafifah; Yektiningtyastuti; Supriyadi Supriyadi (Jurnal Ilmu Keperawatan Maternitas, 2023)
The lifestyle of a large number of young women from various regions with different behaviors, habits, and knowledge in Islamic boarding schools often results in the emergence of various health problems. One of them is the lack of personal hygiene, which the limited facilities and the simultaneous use of toilet facilities by many people cause. Lack of personal hygiene in adolescent girls will trigger various reproductive health problems, including the occurrence of reproductive tract infections with the main symptom of vaginal discharge (fluoralbus). This study aims to determine the relationship between knowledge about fluoralbus and the personal hygiene behavior of adolescent female students of the â€œXâ€ Islamic Boarding School Dukuhwaluh, Purwokerto. This study is a quantitative research with a correlational descriptive design. The research sample consisted of 72 adolescent female students of the â€œXâ€ Islamic Boarding School Dukuhwaluh, Purwokerto, which was taken with a systematic random sampling technique. Univariate analysis uses frequency distribution and percentage for each variable, and bivariate analysis uses the Chi-Square Test. The results showed that the majority of adolescent female students had sufficient knowledge about fluoralbus (63,9%), and had negative personal hygiene behaviors (91,7%). The results of the bivariate analysis showed a p-value of 0,573 (> 0,005), which means that there was no significant relationship between knowledge about fluoralbus and personal hygiene behavior of adolescent female students of the â€œXâ€ Islamic Boarding School Dukuhwaluh, Purwokerto.